A longitudinal study of the turning points and trajectories of therapeutic relationship development in occupational and physical therapy - Ayana Horton; Gail Hebson; David Holman (BMC, 2021)
Abstract Background The importance of the therapeutic relationship is widely recognised across healthcare professions. Despite the importance of therapeutic relationships, there are significant gaps in the knowledge base on how these relationships develop. To address these gaps, this study explores relationship dynamics by identifying relational turning points and trajectories in therapeutic relationships between occupational therapists and physical therapists and their patients. The implications for how a focus on these relational aspects can enhance clinical practice will be discussed. Methods Data collection was based on the Retrospective Interview Technique and consisted of two phases. In the first phase patients and therapists were asked to tell the story of their therapeutic relationship development and as part of this, identify the turning points that occurred. In the second phase, therapists-patient dyads were observed from their first interaction to their last to identify potential turning points and at the end of the relationship a participant verification interview was conducted with both dyadic partners individually. Template analysis was used to analyse the data. Results Therapists identified 6 distinct categories of turning points; Progress Towards Goals, Set-backs in Progress Towards Goals, Interpersonal Affective Bonding with Patients, Interpersonal Problems with Patients, Positive Feedback, and Negative Feedback. Patients identified 5 categories of turning points; Progress Towards Goals, Set-backs in Progress Towards Goals, Interpersonal Affective Bonding with Therapists, Agreement with Therapist and Change in Treatment. These turning points varied regarding their impact on the trajectory of the therapeutic relationship. The trajectory patterns identified were stable, upward, downward, and multidirectional. Conclusion This study makes an important contribution to our understanding of therapeutic relationship dynamics in the occupational and physical therapy context. The results expose the challenges that therapists and patients face in building high-quality therapeutic relationships, the diversity of therapeutic relationships, and how these relationships develop over time. This is the first study to use a turning point analysis in research on therapeutic relationships.